Effect of Physiotherapy on the Motor Recovery and Improvement in Patients with Facial Palsy - Bader, baida (Iraqi National Journal of Nursing Specialties, 2010)
Objectives: The study aims to investigate the efficiency of physiotherapy methods to improve thedegree of the clinical recovery of the peripheral facial palsy.Methodology: This study is carried out at the Rehabilitation Center-Baghdad from November 2009 tillMarch 2010. This study includes (40) patient, their ages are from (13) to (55) years old; (24) male and(16) female with unilateral facial palsy of undetermined cause. House-Brackmann facial recoveryscores have been used before and after the physiotherapy treatment.Results: The results show that the physiotherapy sessions obtained the best effect of the electricalstimulation, exercises and massage in the treatment of facial palsy. Highly respondents in femalescompared to males in the total improvement, highly respondents in partial recovery compared to totalrecovery.Recommendations: The study recommends that the physiotherapists and patients should use thephysiotherapy sessions with follow-up that include stimulation, massage and exercises and completeall sessions of treatment.